2017
DOI: 10.15376/biores.12.3.6237-6250
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Doping of Nitrogen in Bamboo-Based Super Activated Carbon for Hydrogen Storage

Abstract: N-doped microporous activated carbons were synthesized by hydrothermal doping with ammonia as the nitrogen precursor; the chemical, structural, and hydrogen storage properties of the developed activated carbons (ACs) were also examined. The results showed that this method is an effective way of preparing microporous activated carbons with high surface area. Both the surface areas and the N contents of ACs were increased after hydrothermal doping, and hence, the hydrogen storage capacities were improved. The hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The initial Q st values at a low adsorption quantity of 0.1 mmol/g or at the beginning of the adsorption is 35 kJ/mol (when <20 kJ/mol, physical adsorption alone). This value is much higher than the enthalpy of liquefaction of CO 2 (17 kJ/mol) and porous carbon materials, even some nitrogen doping porous carbon materials. ,,,,,, The results indicated that the surface of the PMF carbon cryogels provides a significant improvement over the affinity of the gas itself and a stronger interaction between CO 2 molecules and carbon cryogels. The main reason for the high adsorption heat is the large number of micropores and the interaction between nitrogen-containing functional groups and CO 2 during the initial stage of adsorption. ,,,, However, it must be noted that these values are still much less than the energy required to dissociate covalent bonds, which suggests an effortless reversible process because of the low-energy consumption for desorption.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The initial Q st values at a low adsorption quantity of 0.1 mmol/g or at the beginning of the adsorption is 35 kJ/mol (when <20 kJ/mol, physical adsorption alone). This value is much higher than the enthalpy of liquefaction of CO 2 (17 kJ/mol) and porous carbon materials, even some nitrogen doping porous carbon materials. ,,,,,, The results indicated that the surface of the PMF carbon cryogels provides a significant improvement over the affinity of the gas itself and a stronger interaction between CO 2 molecules and carbon cryogels. The main reason for the high adsorption heat is the large number of micropores and the interaction between nitrogen-containing functional groups and CO 2 during the initial stage of adsorption. ,,,, However, it must be noted that these values are still much less than the energy required to dissociate covalent bonds, which suggests an effortless reversible process because of the low-energy consumption for desorption.…”
Section: Resultsmentioning
confidence: 89%
“…Table shows the S values of all samples, which are in the range of 13–18, indicating that all the carbon cryogels obtained are ideal separation materials of CO 2 /N 2 mixture. This can be explained by the fact that compared with N 2 , CO 2 has greater polarizability and quadrupole moment, and the introduction of nitrogen and oxygen atoms increases the polarity of the material, thereby improving the CO 2 /N 2 selectivity. ,, The adsorption selectivity of CO 2 /N 2 and capacities from these carbon cryogels suggests that it has a higher or comparable selectivity and capacities toward CO 2 than the nitrogen-doped porous carbons from the open literature, ,, which is attributed to the higher surface area, appropriate pore size, and heteroatom doping also. However, it should be mentioned that this CO 2 /N 2 selectivity is still lower than some previous reported results but the CO 2 adsorption capacities are higher. ,,, In addition, to investigate the cyclic stability of PMF-1:2.5, a repeated adsorption test was conducted at 0 °C and 1 bar.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Compared with previous studies, N-doped activated carbon (NAC) demonstrated the best H2 uptake property. [10] Later a 2019 study reported a Pt-N-doped AC with further improved H2 uptake improved. Meanwhile, they also found that the porous structure mainly dominant the H2 uptake ability at traditional 77 K temperature, while the Pt content started to proportionally correlated to the H2 uptake at 298 K. [11]…”
Section: Nitridationmentioning
confidence: 99%